Hubungan Body Image dan Intensitas Penggunaan Media Sosial dengan Kebiasaan Makan pada Remaja Putri di SMAN 1 Kota Serang - Shafa Andini, (2023)
Indonesian adolescents experience nutritional problems, including malnutrition and micronutrient deficiencies. Nutritional problems caused by changes in eating habits which can be influenced by body image and the intensity of social media use. This study aims to determine the association between body image and the intensity of social media use with eating habits in female adolescent at SMAN 1 Kota Serang. This study used a cross-sectional design with a sample of 145 respondents selected using a stratified random sampling technique. Data was collected through Adolescent Food Habits Checklist (AFHC), Body Shape Questionnaire (BSQ-16), and Social Networking Time Use Scale (SONTUS) questionnaire. The variables are eating habits, body image, and intensity (frequency, duration, and intensity) of social media use. Data analysis used chi-square test and fisher's exact test. The results showed that there was an association between body image (p=0,001) and eating habits and there were no association between frequency (p=0,288), duration (p=0,469), and intensity (p=0,715) of social media use and eating habits. The conclusion is that there was an association between body image and eating habits and there were no association between frequency, duration, and intensity of social media use and eating habits of female adolescent.